Trophic ecology of brown trout (Salmo trutta L.) in subarctic lakes - Sanchez-Hernandez, Javier; Amundsen, Per-Arne (Ecology of Freshwater Fish, 2014)
Accepted manuscript version. Published version available in Trophic ecology of brown trout (Salmo trutta L.) in subarctic lakes (2015) 24(1), s.148-161. . In subarctic lake systems, fish species like brown trout are often important predators, and their niche performance is a key characteristic for understanding trophic interactions and food web functioning at upper trophic levels. Here, we studied summer habitat use and stomach contents of brown trout under both allopatric and sympatric conditions in six subarctic lakes to reveal its trophic role, and population- and individual-level niche plasticity. In allopatry, brown trout mainly used the littoral habitat, but less commonly also the pelagic zone. In sympatry with stickleback, there was always a considerable habitat overlap between the two species. In contrast, sympatric populations of brown trout and Arctic charr generally revealed a distinct habitat segregation. In the sympatric systems, there was in general a distinct resource partitioning between the trout and charr, whereas the observed diet overlap between trout and stickleback was much larger. Trout modified their individual dietary specialization between the littoral and pelagic zone, always being lower in the littoral. Piscivorous behaviour of trout was only found in sympatric systems, possibly contributing to a competitive advantage of trout over charr and stickleback. Hence, the trophic level of trout was strongly related to the fish community composition, with a higher trophic level in sympatric systems where piscivorous behaviour was frequent. These changes in the trophic level of trout linked with the observed food resource partitioning might be an important mechanism in the ecosystem functioning of subarctic lakes in order to allow coexistence among sympatric-living fish species.